Lupus erythematosus tumidus: clinical perspectives - Patsinakidis N; Kautz O; Gibbs BF; Raap U (Dove Medical Press, 2019)
Nikolaos Patsinakidis,1,2 Ocko Kautz,1 Bernhard F Gibbs,2 Ulrike Raap1,2 1University Clinic of Dermatology and Allergology, University of Oldenburg, Klinikum Oldenburg Aör, Oldenburg, Germany; 2Division of Experimental Allergy and Immunodermatology, University of Oldenburg, Oldenburg, GermanyCorrespondence: Nikolaos PatsinakidisUniversity Clinic of Dermatology and Allergology, University of Oldenburg, Klinikum Oldenburg AöR, Rahel-Straus-Strasse 10, 26133, Oldenburg, GermanyTel +49 4 414 037 2854Fax +49 441 403 2852Email patsinakidis.nikolaos@klinikum-oldenburg.deAbstract: Lupus erythematosus tumidus (LET) is an uncommon and photosensitive inflammatory skin disorder which is characterised by erythematous urticarial plaques. In the last 20 years, extensive research on clinical and histological aspects of the disease have led to a better characterization of this nosological entity and to differentiate it from other similar or related diseases. Today, LET is considered as a separate subtype of cutaneous lupus erythematosus (CLE) with a benign, intermittent clinical course (intermittent CLE, ICLE) and only rarely associated with systemic lupus erythematosus (SLE).Keywords: lupus erythematosus tumidus, tumid lupus, intermittent cutaneous lupus